Parámetros físico-químicos en aguas costeras de la Isla del Coco, Costa Rica (2001-2007) - Acuña González, Jenaro (2008)
Four cruises to Isla del Coco (Cocos Island), Costa Rica, were carried out in order to gather oceanographic data related to surface temperature, salinity, dissolved oxygen concentration, Secchi disk depth, nutrient concentra tions (nitrate, nitrite, phosphate, and silicate), chlorophyll-a, and suspended materials. Surface temperatures, salinities and dissolved oxygen concentrations were high, in the range of 26.5 to 29.7ºC, 27 to 32 psu, and 102.0 to 127.5% saturation, respectively. Phosphate was always present in the water samples, within the typical range of 0.10 to 0.53 µmol/L; the other nutrients were not detectable in some samples. Chlorophyll-a concentrations were in the range of 0.02 to 0.42 mg/m3 which revealed the influence of oceanic and coastal waters, with the higher phytoplanktonic pigment concentrations near the coast, and suspended materials from 1.08 to 17.91 mg/L.